(untitled) (Journal of Academic Research, 2024)
Power electronics switching converters widely utilize high-frequency magnetic components; inductors and transformers. The efficiency and power density of such converters depend on the design technology of the windings to minimize the high-frequency losses. This paper presents analytical investigation of the skin and proximity effects in the windings, it simulates the AC resistance as a function of the layer thickness. More particularly, the theoretical analysis and simulation of copper foil and Litz windings for high frequency applications are reviewed and discussed. Also, the performance is compared on the basis of the AC resistance factor and leakage inductance. The magnetic components is optimally designed with low ac resistance and leakage inductance to yield higher efficiency and high density switching converters.